Depression and its correlates among undergraduate students in a medical college of West Bengal: A cross-sectional study - Avisek Gupta,; Subarna Sinha Mahapatra,; Sarkar, Dipanwita; Chakraborty, Sohanjan (Asian Journal of Medical Sciences, 2023)
Background: Depression among medical students is still a neglected public health problem in India. Aims and Objectives: This study was conducted to find out the prevalence of depression and its correlates among undergraduate medical students of a medical college of eastern India. Materials and Methods: A cross-sectional descriptive study was conducted among 336 undergraduate students of a Medical College during October 2022–January 2023. A predesigned, pretested, semi-structured, self-administered questionnaire incorporating Beck’s depression inventory scale was used for data collection. Data were analyzed using the trial version of SPSS software version 20.0. Mean, standard deviation, proportion, or percentages were calculated. Chi-square and Fisher’s exact test were used for statistical significance as necessary. For all statistical purposes, P<0.05 was considered statistically significant. Results: Out of the total of 336 students, 205 were male and 131 were female. The mean (SD) age of the study participants was 21.04±1.75 years. More than one-third (39.3%) of the study participants were suffering from depression. Bivariate analysis showed that there was a significant association between depression with certain variables such as gender, quality of relationship with friends, major catastrophic events in the past 3 months, broken relationship, and not opting for MBBS by their own choice. Conclusion: Regular screening for depression, identification of contributory factors of depression and implementing appropriate measures, and follow-up of the affected students are vital. Analytical studies aimed at identifying the risk factors and the effects of depression on the undergraduate medical students are need of the hour.